Regression Model for gamma Lindley distribution with Application: Regression Model for gamma Lindley distribution (Statistics, Optimization & Information Computing, 2026)
The present study introduces a novel regression model where the response variable follows the gamma Lindley distribution. The model's unknown parameters are estimated using the maximum likelihood method. To assess the effectiveness of these estimates, a simulation study is carried out. Furthermore, a residual analysis is conducted to examine the proposed model's adequacy. The gamma Lindley model is compared with other regression models, such as Weibull and gamma regression, based on various statistical criteria. The findings indicate that the proposed model provides a superior fit to the data compared to the alternatives. The model is expected to be applicable in diverse fields, including economics, biological research, mortality and recovery analysis, health studies, hazard assessment, measurement sciences, medicine, and engineering.